2011
DOI: 10.1177/0022034511417442
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate Masticatory Force as a Criterion in Implant Selection

Abstract: Osseointegrated implants often fail because of excessive masticatory forces that cause extremely large stresses in bone tissue. We hypothesized that a proper dental implant could be selected by comparing the ultimate masticatory forces of a wide range of commercially available implants. We determined ultimate oblique masticatory forces for different cylindrical implants, taking into consideration the biomechanical correlation between implant dimensions and stresses in supporting bone. For this purpose, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 22 publications
0
28
0
4
Order By: Relevance
“…In most FE studies [13][14][15][16], stress and strain in bone were evaluated under the maximum occlusal load or a larger load than that in our study. However, in the mechanostat theory, the assumed load is the "typical peak voluntary mechanical loads that refers to the largest repeated and intentional loads on bones exerted by intentional activities during a typical week or month".…”
Section: Loading Conditionsmentioning
confidence: 99%
“…In most FE studies [13][14][15][16], stress and strain in bone were evaluated under the maximum occlusal load or a larger load than that in our study. However, in the mechanostat theory, the assumed load is the "typical peak voluntary mechanical loads that refers to the largest repeated and intentional loads on bones exerted by intentional activities during a typical week or month".…”
Section: Loading Conditionsmentioning
confidence: 99%
“…Another significant factor is bone quality, in mechanical terms; this is determined by bone strength. Increase in implant length and diameter leads to reduction of stress magnitudes within the cortical bone [41]. FEA study shows that non-submerged implants showed higher stress values in the peri-implant bone than submerged ones and the use of soft liner materials considerably reduces the stress levels in the peri-impant bone interfaces.…”
Section: Dental Implants and Anchorage Systems For Tooth Movements Anmentioning
confidence: 95%
“…The failure is associated with bone loss around an implant neck. Bone loss can be activated by excessive implant loading, as by bacterial infection or trauma [41]. Mechanical stress can have positive and negative consequences for bone tissue and for maintaining osseointegration of an oral implant [9].…”
Section: Dental Implants and Anchorage Systems For Tooth Movements Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental implants are currently used to replace missing teeth, to rebuild the craniofacial skeleton, to provide anchorage during orthodontic treatments and even to help new bone formation in the process of distraction osteogenesis [3]. Biocompatible titanium and titanium alloys materials are used for dental implants for their excellent corrosion resistance and suitable mechanical properties [4]. Although titanium implants available commercially at present have got many disadvantages such as mismatches between the elastic modulus of the implant and of the bone, di erent bonding strength between the implant and the bone [5].…”
Section: Introductionmentioning
confidence: 99%